Exploring the potential of zinc-solubilizing Bacillus strains to enhance rice (Oryza sativa L.) productivity in nutrient-deficit soils - Ahmad, Maqshoof; Naseer, Iqra; Nazli, Farheen; Dar, Abubakar; Sarfraz, Rubab; Zulfiqar, Usman; El-Beltagi, Hossam S.; Saleh, Muneera A.; Rebouh, Nazih Y.; Rasulov, Xasanboy; Prasad, PV Vara (Frontiers in Microbiology, 2025)
IntroductionFood and nutritional security remain a significant challenge among the food-insecure people around the world, facing a lack of nutritious food rather than food availability alone. Micronutrient deficiencies in staple grains present a serious public health issue, especially impacting millions of women and children in developing nations. Staple cereals contain low concentrations of micronutrients, especially zinc (Zn).MethodologyThe present study explored the potential of zinc-solubilizing Bacillus strains to improve rice (Oryza sativa L.) growth, antioxidant activity, yield, and quality in a completely randomized design (CRD) with four replications. For this purpose, four pre-isolated, characterized and identified Bacillus strains (AN24, AN30, AN31, and AN35) were evaluated separately, as well as in co-inoculation on the growth promotion of rice cultivar PK 386.ResultsThe results showed that the co-inoculation of Bacillus strains improved the growth and yield of rice more effectively than individual bacterial strains. Furthermore, co-inoculation was also more efficient in improving the soil nutrient status and biology (microbial populations) on which rice plants were grown in the pot experiment. In addition to improvement in plant growth parameters, the co-inoculation of Bacillus strains improved the N, P, K, Fe, and Zn up to 26, 30, 29, 19, and 27%, respectively, in rice grains as compared to control, along with improvement in macro and micronutrients in rice straw and roots. Co-inoculation also improved the crude protein in rice grains by 27% compared to the un-inoculated control.DiscussionThese results suggest that co-inoculated Bacillus megaterium strains AN24 and B. AN31offer a promising, eco-friendly alternative to synthetic fertilizers and can play a vital role in addressing micronutrient deficiencies in cereals.Future directionsFurther molecular characterization of Zn solubilizing genes and field-scale evaluations are recommended to validate their efficacy under diverse agroecological conditions. The combination could be further evaluated as a valuable tool for developing biofertilizers to improve rice productivity and quality in nutrient-deficient soils.